INFLUENCE OF PHYSICO-CHEMICAL PARAMETERS ON SECONDARY METABOLITE PRODUCTION BY MARINE FUNGI - G., Anuhya; V., Jyostna; Yvv, Aswani Kumar; B., Bodaiah; P., Sudhakar (International Journal of Current Pharmaceutical Research, 2017)
Objective: Our study aimed to characterize and optimize the physico-chemical properties which render the high yield of bioactive secondary metabolites from marine fungi and its antibacterial activity against clinical pathogens. Methods: Bioactive secondary metabolites extracted from marine fungi of Nijampatnam mangroves, Guntur district Andhra Pradesh, India. By using different solvent systems, secondary metabolite was screened for antimicrobial activity against clinical pathogen, Optimization of cultural conditions for maximizing the yield of biomass and compared the yield in different broth media and minimum inhibitory concentration of the optimised compound done for both compounds. Results: fungal extracts GAPS-1 and GAPS-2 was affectively extracted in ethyl acetate. Isolated compound showed antibacterial activity highest zone of inhibition against E. coli and least to Pseudomonas. Maximum yield of the compound was achieved in modified potato dextrose broth (PDB) medium containing 20% w/v Potato 2% w/v Dextrose broth containing1% w/v glucose and sucrose,1% w/v beef extract and ammonium chloride and 0.01 % mineral salts(MGSO4 and MNSO4) at 25 Â°C and 30 Â°C and pH 7.0 and 8.0 with 144 h of incubation period. The yield was observed maximum in potato dextrose broth compared to czapek dox broth, sabaraud's broth and nutrient broth and minimum inhibitory concentration of the optimized compound ranges from 250 Î¼g for gaps-1 and 300 Î¼g for gaps-2. Conclusion: Secondary metabolite yield maximum in potato dextrose broth and its potential anti-bacterial activity needs further investigation for pharmaceutical applications.